Effectivity test of application of Serai (Cymbopogon citratur)) and Chemical Repellents against Mosquito (Aedes aegypti) - Safrida, Safrida; Elfira, Dzulka; -, Dian; -, Shella; -, Sabilla (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2021)
In the rainy season the mosquitoes grow faster than during the dry season, especially the growth of the mosquito that causes dengue fever, namely the Aedes aegypti mosquito. One way to avoid contact with mosquitoes is to use a repellent. Repellant is a chemical or non-chemical which has the ability to interfere with the ability of an insect to recognize attractant chemicals of animal or human origin, or to prevent the biting insect from landing. Lemongrass (Cymbopogon citratus) is one of the essential oil-producing plants. In Indonesia, a species that is better known is West Indian Lemongrass and people generally use it as a mixture of herbs and spices because it has a distinctive aroma like lemon, this aroma is obtained from the citral compounds contained in lemongrass essential oil. This study used an experimental method with a completely randomized design consisting of 6 treatments and 3 replications. The results of research conducted on the effect of lemon grass juice on the bite of Aedes aegypti mosquitoes using a control and a concentration of 1%, 2%, 3%, 4% with observation 5 minutes with 3 replications. The results of observations after spraying citronella juice (Cymbopogon citratus) against rabbits at a concentration of 1% and 2% there were Aedes aegypti mosquitoes that bit even though only a little with a protective power of 78% -88%, while at a concentration of 3% -4% there was no one Aedes aegypti mosquito that bites with 100% protection power.